Self-propulsion of flapping bodies in viscous fluids: Recent advances and perspectives - Wang, Shizhao; He, Guowei; Zhang, Xing (Acta mechanica Sinica, 2016)
Flapping-powered propulsion is used by many animals to locomote through air or water. Here we review recent experimental and numerical studies on self-propelled mechanical systems powered by a flapping motion. Thesestudies improve our understanding of the mutual interaction between actively flapping bodies and surrounding fluids. The results obtained in these works provide not only new insights into biolocomotion but also useful information for the biomimetic design of artificial flyers and swimmers.